Concurrent purification of phycobiliproteins from Leptolyngbya sp. and their selective enhancement in response to different wavelengths of LED light. (February 2023) - Prabha, Syama; Vijay, Aravind K.; Devarajan, Anjali; George, Basil
Abstract: The present study identifies freshwater cyanobacterium Leptolyngbya sp. CMSACR2013 as a potential producer of phycobiliproteins. Concurrent purification of phycobiliproteins using the three-stage ammonium sulfate precipitation technique was employed to recover phycocyanin and phycoerythrin simultaneously. This was followed by anion exchange chromatography, resulting in an analytical grade C-phycoerythrin (Purity = 4.6) and reactant grade C-phycocyanin (Purity = 3.5). Moreover, to understand the relative pigment production in Leptolyngbya sp., the cultures were exposed to different wavelengths of LED lights and cultivated for 28 days. C-phycoerythrin content was higher under green light (74.77 mg L −1 ). In contrast, C-phycocyanin and C-allophycocyanin were higher under red light (72.94 mg L −1 and 63.50 mg L −1 ). The results also revealed the highest biomass content under red light (2.20 g L −1 ). These results suggest exploiting the complementary chromatic adaptation exhibited by the strain to improve the selective accumulation of phycobiliproteins. Graphical abstract: Unlabelled Image Highlights: Leptolyngbya sp. as novel strain for the production of multiple phycobiliproteins Concurrent C-PC and C-PE separation by a simple non-chromatographic method Obtained analytical grade C-PE (Purity = 4.6) and reactant grade C-PC (Purity = 3.5) Identified the complementary chromatic adaptation in Leptolyngbya using LED light Red and green led lights enhanced C-PE and C-PC productivity respectively.